2016
DOI: 10.1002/ange.201608715
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Carbonylative Synthesis of Chromenones from Simple Phenols and Internal Alkynes at Atmospheric Pressure

Abstract: Anovel procedure on the carbonylative synthesis of chromenones has been developed. With simple phenols and internal alkynes as the substrates,v arious chromenones were isolated in moderate to good yields with excellent regioselectivity and functional-group tolerance by using iridium as the catalyst and copper as the promotor at atmospheric pressure. Notably,t his is the first example on carbonylative annulation of simple phenols and alkynes.Coumarin was first isolated by Vogel in 1820 as an atural product from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Figure 2 shows that cinnamates 1a-m cyclise in the presence of ligand-free Pd 3-4 catalysts to give the corresponding α coupled, exo-benzylenyl δ-lactones 2a-m in excellent yields and reasonable stereoselectivity, with the E isomer as the major product. These results strongly support that exo regioselectivity takes control and violate the long accepted β-directing electronic rules for the Mizoroki-Heck reaction in aryl iodide-substituted cinnamyl esters 1a(a)-m, with catalytic Pd 3-4 clusters, to intramolecularly couple the α carbon atom of the electron-poor alkene to the aryl iodide, and give otherwise difficult to prepare exobenzylidene lactones 2a(a)-m 17,18 .…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Figure 2 shows that cinnamates 1a-m cyclise in the presence of ligand-free Pd 3-4 catalysts to give the corresponding α coupled, exo-benzylenyl δ-lactones 2a-m in excellent yields and reasonable stereoselectivity, with the E isomer as the major product. These results strongly support that exo regioselectivity takes control and violate the long accepted β-directing electronic rules for the Mizoroki-Heck reaction in aryl iodide-substituted cinnamyl esters 1a(a)-m, with catalytic Pd 3-4 clusters, to intramolecularly couple the α carbon atom of the electron-poor alkene to the aryl iodide, and give otherwise difficult to prepare exobenzylidene lactones 2a(a)-m 17,18 .…”
Section: Resultssupporting
confidence: 60%
“…Different representative Pd complex catalysts 15 (2 mol%) for the Mizoroki-Heck reaction gave low yields of product 2a, under optimal reaction conditions for their respective catalytic activity (entries 1-15), however, in-situ generated catalytic ligand-free ultrasmall Pd 3-4 clusters 16 gave significant amounts of the α product 2a (entries [16][17][18][19][20], up to a 69% yield by gas chromatography (GC, as a 4:1 mixture of E and Z isomers, see Supplementary Figure 1) and with an isolated yield after column chromatography of 52% for the α−E product 2a and <10% for the β coupling product 3a. The cinnamic ester 1aa, with an additional carbon atom in the alkyl chain, was also prepared and tested as a starting material for the coupling, and the result showed that the α coupling product, the unfavored seven-member ring ε-lactones 2aa and 2ab were formed in 55% isolated yield, without any trace of β coupling product 3aa (entry 21, see also Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a novel carbonylative synthesis of chromenones from simple phenols and internal alkynes was developed by Wu and co-workers. 35 The reaction was performed at atmospheric pressure of CO; a number of chromenones were isolated in moderate to good yields with excellent regioselectivity and functional-group Besides arenes, alkenes have also been successfully carbonylatively activated. In 2016, Gaunt and co-workers developed a general carbonylation procedure for the preparation of b-lactams.…”
Section: Scheme 5 Synthesis Of Linear Amines From Alkenesmentioning
confidence: 99%
“…More recently, we reported an iridium-catalyzed carbonylative cyclization of simple phenols with internal alkynes to produce chromenones. 9 The selectivity can be tuned by choosing the proper phosphine ligand. However, only disubstituted products can be obtained and we failed with terminal alkynes.…”
mentioning
confidence: 53%